USE OF SECONDARY MATERIALS IN ARCHITECTURE AND CONSTRUCTION - Oleksyn, Mariia; Obynochna, Zoriana (Theory and practice of design, 2023)
The article deals with the topical issue of the use of secondary raw materials in architecture and construction. After conducting an analysis of the world and domestic experience in the use of secondary materials, the existing methods of processing and ways of using raw materials, features and advantages of materials were revealed. The structures and materials listed are not only examples from the Internet, there are a large number of enterprises in Ukraine that manufacture products from recycled waste. It is about the importance, expediency and methods of using secondary raw materials in architecture and construction, given the trends towards greening in the world, and the destruction of existing structures during the war in Ukraine. Goal. Analyze the use of secondary raw materials in architecture and construction. Methodology. The methodological apparatus is based on empirical (method of expert evaluations) and theoretical (critical analysis, complex analysis of factors and influencing factors) research methods. The results. Examples of the possible use of secondary raw materials are given on the basis of the above-mentioned methodology. The article highlights successful resource reuse options and points out that the use of secondary materials in construction contributes to the reduction of carbon emissions and reduces the consumption of natural resources, which are important aspects in the context of today’s requirements for sustainable construction. In general, the results of the article confirm that the use and research of secondary raw materials in the construction and architecture of Ukraine has potential for development. Scientific novelty. In general, the topic of secondary raw materials in construction and architecture is new for Ukraine. In the countries of the European Union, this base has been developed much more powerfully, in many countries even at the legislative level. The article contains a list of structural parts of buildings and materials that should be used in one place or another, and also considers the economic and ecological aspects of the use of secondary raw materials. Practical significance. The formed list will help novice architects to acquire knowledge about secondary materials and the possibilities of their use, because the article offers concrete examples.